DEVELOPMENT OF THEMATIC STUDENTS WORK SHEET (LKPD) BASED ON 21th CENTURY COMPETENCY THEME 7 SUBTHEME 1 LEARNING 1 CLASS V SD LEDUG STATE - Ainun Fitri Nur Khasanah; Sony Irianto; Arifin Muslim (JURNAL HANDAYANI PGSD FIP UNIMED, 2020)
Abstract:This study aims to produce a Student Worksheet (LKPD) based on 21st century student competence theme 7 subtheme 1 learning 1 in class V SDN Ledug. This research is a development study with development procedures according to Thiagarajan, Semmel and Semmel which include: defining, design, developing, disseminating. The results of this study indicate that: (1) Development of Thematic LKPD based on 21st Century Student Competencies Theme 7 Subtheme 1 Learning 1 in grade V of primary schools can be used as teaching material that can be used to supplement thematic teaching materials in primary schools, (2) Assessment validation of experts / experts on the results of the development of LKPD obtained an average of 4.1, which means valid, (3) Teacher's assessment of Thematic LKPD based on 21st Century Student Competencies Theme 7 Subthemes 1 Learning 1 in class V gained an average of 4.5 which included in the category of "Very Good", (4) Students' responses to Thematic LKPD based on 21st Century Student Competence Theme 7 Subtheme 1 Learning 1 in class V obtained an average of 3.6 which means "Very Agree". Keywords: LKPD, Thematic, 21st Century Student CompetenciesAbstrak: Penelitian ini bertujuan untuk menghasilkan Lembar Kerja Peserta Didik (LKPD) berbasis kompetensi peserta didik abad 21 tema 7 subtema 1 Pembelajaran LG1 di kelas V SDN Ledug. Penelitian ini merupakan penelitian pengembangan dengan prosedur pengembangan menurut Thiagarajan, Semmel dan Semmel yang meliputi:pendefinisian (define), desain (design), pengembangan (developm), penyebaran (disseminate). Hasil penelitian ini menunjukan bahwa: (1) Pengembangan LKPD Tematik berbasis Kompetensi Peserta Didik Abad 21 Tema 7 Subtema 1 Pembelajaran 1 di kelas V sekolah dasar dapat dijadikan sebagai bahan ajar yang dapat digunakan untuk melengkapi bahan ajar tematik di sekolah dasar, (2) Penilaian validasi pakar/ ahli terhadap hasil pengembangan LKPD memperoleh rata-rata 4,1 yang berarti valid, (3) Penilaian guru terhadap LKPD Tematik berbasis Kompetensi Peserta Didik Abad 21 Tema 7 Subtema 1 Pembelajaran 1 di kelas V memperoleh rata-rata 4,5 yang termasuk dalam kategori “Sangat Baik”, (4) Respon peserta didik terhadap LKPD Tematik berbasis Kompetensi Peserta Didik Abad 21 Tema 7 Subtema 1 Pembelajaran 1 di kelas V memperoleh rata-rata 3,6 yang berarti“Sangat Setuju”.Kata Kunci: LKPD, Tematik, Komptensi Peserta Didik Abad 21